2016
DOI: 10.1016/j.agwat.2016.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Water balance implications of switching from continuous submergence to flush irrigation in a rice-growing district

Abstract: Studies conducted at the field scale report significant reductions in the irrigation requirements of rice when continuous submergence (CS) is replaced by less water-demanding regimes such as flush-irrigation (FI, i.e. intermittent irrigations of rice growing in non-submerged soils). However, the effects of their extensive application in paddy areas with shallow groundwater is much less studied. We present a scenario analysis investigating the impacts on irrigation requirements induced by a shift from CS to FI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 25 publications
1
26
1
2
Order By: Relevance
“…A strong orientation to agriculture characterizes the area, with the 0.59 hectares of utilizable agricultural area available per With more than 80,000 ha in 2015 [39], the province is the first area in Italy for rice production, though other irrigated crops are also present, from maize to permanent grasslands and short rotation forestry (i.e., poplar groves). This combination in the production pattern may determine conflict in the use of water resource [25], given the specific water demand during the cropping season and the weather-climate trend; despite this, the largest part of irrigation water is here required by rice, since it is the most spread irrigated crop. In this sense, interventions targeted to this sector would have strongly repercussions on regional agriculture as a whole.…”
Section: The Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…A strong orientation to agriculture characterizes the area, with the 0.59 hectares of utilizable agricultural area available per With more than 80,000 ha in 2015 [39], the province is the first area in Italy for rice production, though other irrigated crops are also present, from maize to permanent grasslands and short rotation forestry (i.e., poplar groves). This combination in the production pattern may determine conflict in the use of water resource [25], given the specific water demand during the cropping season and the weather-climate trend; despite this, the largest part of irrigation water is here required by rice, since it is the most spread irrigated crop. In this sense, interventions targeted to this sector would have strongly repercussions on regional agriculture as a whole.…”
Section: The Study Areamentioning
confidence: 99%
“…The irrigation volume applied actually consists in providing more water than the amount needed, which means draining the excess [25,46]. Such water outflow from the field should not be however considered a loss; rather, water surplus is reused in either downstream or adjacent fields, and thus contributes in their irrigation, either by flooding irrigation or not.…”
Section: Water Management Optionsmentioning
confidence: 99%
“…Although the main objective of the rice farms is productive, areas in which the prevailing crop is rice create a peculiar agro-ecosystem characterised by the presence of water in the fields for several months each year (Leibundgut and Kohn, 2014). This extensive water presence endows these areas with significant landscape and natural heritage values, ranging from the preservation of traditional rural landscapes to the safeguarding of different animal and plant species typical of wetland areas (Cesari de Maria et al, 2016). The prolonged presence and circulation of water due to continuous flooding of fields from wet-sowing until close to harvest represent a distinguishing feature of these rice areas, some of which have also been included in the European ecological network NATURA 2000 and on the official list of the European Special Protected Areas (Habitat Directive, 92/43/EEC; European Commission, 1992) (Chiaradia et al, 2013).…”
Section: Rice Irrigation Features In the Italian Agricultural Contextmentioning
confidence: 99%
“…The pedo-climatic conditions are favorable for extensive cropping, but farming is strongly dependent on irrigation due to the high water requirements of these crops. By studying twelve years of meteorological data (from 1993 to 2013) from 10 agro-meteorological stations located in the district, Cesari de Maria et al [2] found that during the agricultural season (April to September), the average temperature was approximately 20.2 • C, while the total rainfall was approximately 360 mm, with marked variability from year to year. The relative humidity was always high (>80%) and implies the presence of foggy months during the winter and hot and muggy months in the summer.…”
Section: The Est Ticino-villoresi Districtmentioning
confidence: 99%
“…In sizeable areas of the southern Member States, especially in Catalonia, Northern Italy and Portugal, gravity-fed surface irrigation remains the dominant form of irrigation, being used in 51%, 70% and 63% of farms, respectively [1]. The main cultivated crops are cereals, particularly maize and rice, which require approximately two to three times the amount of water compared with other extensive crops [2]. The utilized agricultural area (UAA) in these states accounts for approximately 40% of the total land area, resulting in an average size of 16.1 ha per agricultural holding.…”
Section: Introductionmentioning
confidence: 99%